2022 21st International Conference on Micro and Nanotechnology for Power Generation and Energy Conversion Applications (PowerME 2022
DOI: 10.1109/powermems56853.2022.10007567
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modelling Approach for a Piezoelectric Bistable Energy Harvester Architecture

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…2. This VEH (for more details on its design, see [29]) consists of buckled steel beams of length L to which a proof mass M is attached that can oscillate between two stable equilibrium positions, −xw and xw. The VEH is driven by a sinusoidal excitation with a driving frequency f d = ω d /2π and a constant acceleration amplitude A.…”
Section: Bistable Veh Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…2. This VEH (for more details on its design, see [29]) consists of buckled steel beams of length L to which a proof mass M is attached that can oscillate between two stable equilibrium positions, −xw and xw. The VEH is driven by a sinusoidal excitation with a driving frequency f d = ω d /2π and a constant acceleration amplitude A.…”
Section: Bistable Veh Modelmentioning
confidence: 99%
“…(a) Schematic representation of the bistable VEH. (b) Experimental prototype from[29] with dynamics described by(1).…”
mentioning
confidence: 99%
“…The nonlinear VEH considered in this study, shown in figure 6, was designed by Benhemou et al [14]. It consists of a bistable mechanical oscillator with mass M, composed of buckled steel beams of length L. The oscillator has two stable equilibrium positions located at x = ±x w .…”
mentioning
confidence: 99%